Liderazgo educativo y retos de la educación superior en el siglo XXI: hacia la visión y la acción - Ana Monge (Universidad Nacional, Costa Rica, 2003)
In this article, we are developing some ideas and proposals for an educational leadership exercise in order to assume higher education´s main challenges in the XXI century. In this reflection we are taking into consideration the universities´commitments in the construction of more fair and equitable societies according to its necessities and demands in a historical moment distinguished by globalization and scientific technological development. Therefore, we have to emphasize the permanent links between education and economic and social development; besides, we take back some of the ideas presented at the higher education world conference in 1998, which evidenced the implications of the main challenges that education faces in the XXI century. For that reason it is of vital importance, a type of leadership that responds effectively to those challenges through belligerent, participative and precise actions.